2001
DOI: 10.1007/s003830000515
|View full text |Cite
|
Sign up to set email alerts
|

Surgical closure of patent ductus arteriosus in very-low-birth-weight infants

Abstract: In many very-low-birth-weight (VLBW) infants the ductus arteriosus fails to close spontaneously, and they subsequently develop signs and symptoms of poor tissue perfusion and heart failure. This study evalutes the results of early surgical closure of patent ductus arteriosus (PDA). We retrospectively reviewed the records of all 101 VLBW infants who weighed 1,500 g or less when their PDA was surgically ligated in Turku University Hospital between 1988 and 1998. The mean gestational age at birth was 27.2 weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…Thirty-two studies that satisfied the inclusion criteria were included in the analysis (Fig 1). OCEBM levels of evidence varied from level 3 (9 studies) [9][10][11][14][15][16]20,23,26 to level 4 (23 studies) [6][7][8]12,13,[17][18][19]21,22,24,25,[27][28][29][30][31][32][33][34][35][36][37] ( Table 1). Occurrence of UVFP, type of surgery, patient demographics, and vocal fold assessment are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-two studies that satisfied the inclusion criteria were included in the analysis (Fig 1). OCEBM levels of evidence varied from level 3 (9 studies) [9][10][11][14][15][16]20,23,26 to level 4 (23 studies) [6][7][8]12,13,[17][18][19]21,22,24,25,[27][28][29][30][31][32][33][34][35][36][37] ( Table 1). Occurrence of UVFP, type of surgery, patient demographics, and vocal fold assessment are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…7,8,[10][11][12][13][14][15]17,20,21,24,[27][28][29][30][31][34][35][36][37] The weighted pooled proportion was 8.7% (95% CI, 5.4% to 12.6%) (Fig 3). Heterogeneity analysis measured an I 2 of 81.6% (95% CI, 65.0% to 88.4%).…”
Section: Analysis By Type Of Surgerymentioning
confidence: 99%
“…The postoperative mortality after PDA ligation that is directly attributable to the surgical procedure (ie, hemorrhage) is consistently reported to be approximately 1%-3% [9,[15][16][17]. However, overall mortality in premature infants after PDA ligation is significantly higher.…”
Section: Discussionmentioning
confidence: 98%
“…Surgical ligation of PDA is considered standard treatment for symptomatic infants who do not respond to treatment with indomethacin. Since the first reported PDA ligation by Gross in 1938, numerous studies have shown PDA ligation to be both technically feasible and safe, even in premature, low-birth-weight infants [3][4][5][6][7][8].…”
mentioning
confidence: 99%